Isolation and Characterization of Fengycins Produced by Bacillus amyloliquefaciens JFL21 and Its Broad-Spectrum Antimicrobial Potential Against Multidrug-Resistant Foodborne Pathogens - Lin, Long-Zhen; Zheng, Qian-Wang; Wei, Tao; Zhang, Zi-Qian; Zhao, Chao-Fan; Zhong, Han; Xu, Qing-Yuan; Lin, Jun-Fang; Guo, Li-Qiong (Frontiers in Microbiology, 2020)
The continuing emergence and development of pathogenic microorganisms that are resistant to antibiotics constitute an increasing global concern, and the effort in new antimicrobials discovery will remain relevant until a lasting solution is found. A new bacterial strain, designated JFL21, was isolated from seafood and identified as B. amyloliquefaciens. The antimicrobial substance produced by B. amyloliquefaciens JFL21 showed low toxicity to most probiotics but exhibited strong antimicrobial activities against multidrug-resistant foodborne pathogens. The partially purified antimicrobial substance, Anti-JFL21, was characterized to be a multiple lipopeptides mixture comprising the families of surfactin, fengycin, and iturin. Compared with commercially available polymyxin B and Nisin, Anti-JFL21 not only could exhibit a wider and stronger antibacterial activity toward Gram-positive pathogens but also inhibit the growth of a majority of fungal pathogens. After further separation through gel filtration chromatography (GFC), the family of surfactin, fengycin, and iturin were obtained, respectively. The results of the antimicrobial test pointed out that only fengycin family presented marked antimicrobial properties against the indicators of L. monocytogenes, A. hydrophila, and C. gloeosporioides, which demonstrated that fengycins might play a major role in the antibacterial and antifungal activity of Anti-JFL21. Additionally, the current study also showed that the fengycins produced by B. amyloliquefaciens JFL21 not only maintained stable anti-Listeria activity over a broad pH and temperature range, but also remained active after treatment with ultraviolet sterilization, chemical reagents, and proteolytic enzymes. Therefore, the results of this study suggest the new strain and its antimicrobials are potentially useful in food preservation for the biological control of the multidrug-resistant foodborne pathogens.